Emerging Liver–Kidney Interactions in Nonalcoholic Fatty Liver Disease. Issue 10 (October 2015) - Musso, Giovanni; Cassader, Maurizio; Cohney, Solomon; Pinach, Silvia; Saba, Francesca; Gambino, Roberto
<x xml:space="preserve">Abstract</x> Mounting evidence connects non-alcoholic fatty liver disease (NAFLD) to chronic kidney disease (CKD). We review emerging mechanistic links between NAFLD and CKD, including altered activation of angiotensin converting enzyme (ACE)-2, nutrient/energy sensors sirtuin-1 and AMP-activated kinase, as well as impaired antioxidant defense mediated by nuclear factor erythroid 2-related factor-2 (Nrf2). Dietary fructose excess may also contribute to NAFLD and CKD. NAFLD affects renal injury through lipoprotein dysmetabolism and altered secretion of the hepatokines fibroblast growth factor-21, fetuin-A, insulin-like growth factor-1, and syndecan-1. CKD may mutually aggravate NAFLD and associated metabolic disturbances through altered intestinal barrier function and microbiota composition, the accumulation of uremic toxic metabolites, and alterations in pre-receptor glucocorticoid metabolism. We conclude by discussing the implications of these findings for the treatment of NAFLD and CKD.